2006
DOI: 10.1002/bip.20538
|View full text |Cite
|
Sign up to set email alerts
|

Modeling H3 histone N‐terminal tail and linker DNA interactions

Abstract: Molecular dynamics computer simulations were performed for the 25-residue N-terminal tail of the H3 histone protein in the proximity of a DNA segment of 10 base pairs (bp), representing a model for the linker DNA in chromatin. Several least biased configurations were used as initial configurations. The secondary structure content of the protein was increased by the presence of DNA close to it, but the locations of the secondary motifs were different for different initial orientations of the DNA grooves with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The tip helix was more stable than the middle helix during our simulations. A similar propensity for α-helical content in various shorter lengths of the H3 N-terminal tails was reported using MD [17, 18], while two α-helices, one between K4 and K9 and a second between K14 and R26, have been observed in the N-terminal tail of H3 during a MD simulation of the nucleosome [21]. CD experiments indicated that the H3 and H4 tails contributed to the α-helical character of the nucleosome [15, 16], and an X-ray crystal structure of the double PHD finger domain of MOZ/MYST3 in complex with three histone H3 tail isomers, including an unmodified isomer, showed an α-helical conformation between K4 and T11 in the H3 tail [51].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The tip helix was more stable than the middle helix during our simulations. A similar propensity for α-helical content in various shorter lengths of the H3 N-terminal tails was reported using MD [17, 18], while two α-helices, one between K4 and K9 and a second between K14 and R26, have been observed in the N-terminal tail of H3 during a MD simulation of the nucleosome [21]. CD experiments indicated that the H3 and H4 tails contributed to the α-helical character of the nucleosome [15, 16], and an X-ray crystal structure of the double PHD finger domain of MOZ/MYST3 in complex with three histone H3 tail isomers, including an unmodified isomer, showed an α-helical conformation between K4 and T11 in the H3 tail [51].…”
Section: Discussionsupporting
confidence: 77%
“…Earlier simulations on isolated peptides showed hints of α-helical content within the H3 tail. However, these simulations were performed on limited timescales and not on the full-length tail [17, 18]. In the study by Liu and coworkers [18], they established that a shortened H3 tail peptide (residues 1–25) contained an α-helix and also, interestingly, that the dual dimethylation and acetylation of H3K4 and H3K9 had an effect on the stability of the helical content of the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…However, at present increasing experimental evidence favors the possibility that histone tails could be structured. Supporting this idea, it has been proposed, using circular dichroism or molecular dynamics computer simulations, that histone H3 N-terminal tails can adopt an ␣-helical conformation when bound to DNA (3,28). This binding to DNA occurs principally in interphase but is reduced in mitosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…28,2008 MITOTIC H3 TAILS ADOPT DIFFERENT CONFORMATIONS 1749 protein A. For the two antibodies, the labeling was specifically restricted to metaphasic chromosomes and was distributed all over the chromosome section (Fig.…”
Section: Vol 28 2008 Mitotic H3 Tails Adopt Different Conformationsmentioning
confidence: 97%
“…Of the computational work reported so far, much of the focus has been on components of the nucleosome and unmodified histone tail peptides. There are some studies of the interaction of DNA with unmodified histone tail peptides, [17][18][19] and of the complete nucleosome core. [20][21][22] Computational studies of chromatin compaction, and, in particular, the role played by histone tails have also been performed using coarse-grained models and Monte-Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%